?MIXED LIGAND COMPLEXES INCLUDING COMPLEXES OF TETRA- AZAMACROCYCLES (Biological Sciences - PJSIR, 1996)
Several new mixed ligand complexes of zirconium (IV),uranium (VI),copper (II)and zinc (II)ofcompositions, [Zr(0)CI2UUI] [L'eo-phenylenediamine, ethylenediamine, I,6-diaminohexane and UI=quinoline, pyridine pyridine N-oxide and aniline]; [Zr(0)CI22ULll] [L'eaniline and L'I=pyridine N-oxide]; [Zr(0)[14] ane N4CI]CI; [U(0)2 [14] ane N4] (N03)z and [ML]XJM=Cu(II) and Zr(II), Letrans-fl d] -diene and X=CI' and N03'] have been synthesised and characterized. Conductivity measurements reveal that complex 1is nonelectrolyte and copper (II) and zinc (II) complexes are 2:1electrolytes in DMSO. But such measurementscould notbecarried out for other complexes due to their insolubility in almost all common organic solvents.Magnetic measurements, IR and electronic spectral data are consistent with octahedral geometry of zirconium.(IV) and uranium (VI) complexes and four-coordinated square planar geometry of copper (II) and zinc (II)complexes.